2018
DOI: 10.1509/jmr.15.0559
|View full text |Cite
|
Sign up to set email alerts
|

Double Mental Discounting: When a Single Price Promotion Feels Twice as Nice

Abstract: This research finds that when a single gain has strong associations with multiple costs, consumers often mentally deduct that gain from perceived costs multiple times. For example, with some price promotions (e.g., spend $200 now and receive a $50 gift card to spend in the future), consumers mentally deduct the value of the price promotion from the cost of the first purchase when they receive the promotion, as well as from the cost of the second purchase when they use the promotion. Multiple mental deductions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…This belief reduces net savings flows. Cheng and Cryder (2018) find that making it mentally harder to tie a gain to multiple costs mitigates the double-counting effect. In the same way, the act of designating whether a dollar of savings is intended for short-term versus long-term use, or for ordinary current expenses versus rainy-day expenses, may force a recognition that a dollar can only be spent once.…”
Section: The Case For Rainy-day Savings Accountsmentioning
confidence: 87%
See 1 more Smart Citation
“…This belief reduces net savings flows. Cheng and Cryder (2018) find that making it mentally harder to tie a gain to multiple costs mitigates the double-counting effect. In the same way, the act of designating whether a dollar of savings is intended for short-term versus long-term use, or for ordinary current expenses versus rainy-day expenses, may force a recognition that a dollar can only be spent once.…”
Section: The Case For Rainy-day Savings Accountsmentioning
confidence: 87%
“…First, having a separate rainy-day account enforces discipline in recognizing what savings can and cannot do. Cheng and Cryder (2018) show that when a single gain can be mentally associated with multiple costs (the scenario they study is a promotional gift card received if a purchase is made; the card balance is then associated with both the original purchase and the future purchase), individuals double-count the gain and end up spending more. Analogously, when a single savings account serves multiple purposes, it may be easy to engage in a sort of self-deception, believing that a dollar saved that could be used to cover either a short-term financial shock or retirement consumption is in fact available to finance both.…”
Section: The Case For Rainy-day Savings Accountsmentioning
confidence: 99%
“…It would be worthwhile for managers to observe how such effects influence product choices alongside other competing logo and front-of-pack elements as well as to explore other potential mediators, such as complexity or novelty. Similarly, researchers have discussed consumer perceptions about price information and promotion bundles (e.g., cash back, points; e.g., Cheng and Cryder 2018). Our model could offer insights into consumer heterogeneity inherent in the holistic perceptions of product value and quantify how these mediate choice.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…Future research should also consider the behavioral benefits consumers may derive from rebates. For example, Cheng and Cryder (2018) found that consumers may benefit twice from a rebate (double mental discounting): once when they purchase the item and deduct the amount of the rebate from the retail price, and a second time when they actually receive the rebate. Future research may also consider alternative strategies to increase profits through rebates that are applied to bundle purchases (Popkowski Leszczyc & Häubl, 2010;Jeitschko, Jung, & Kim, 2017), or upgrade-rebate strategies used to stimulate sales for new generations of products, such as a new iPhone (Avagyan, Esteban-Bravo, & Vidal-Sanz, 2016).…”
Section: Summary and Implicationsmentioning
confidence: 99%